Caracterización lanera de majadas ovinas en sistemas trashumantes de Trancas (Tucumán) - Riva de Neyra, Leonardo Atilio; Jorrat, Juan José; Prado, José María; Cantarella, Gabriela Eugenia; Gómez, María Florencia; Paez, Juan Pablo; Homse, Lisandro (Asociación Argentina de Producción Animal, 2021)
Póster